Factors Associated with Breast Self-examination Behaviors among Women Workers - Chamnanchang, Sutharat; Priyatruk, Panudda; Moopayak, Kanokporn (Nursing Science Journal of Thailand, 2014)
Purpose: This study was aimed at investigating factors related to breast self-examination behaviors including predisposing factors: knowledge of breast cancer, attitude toward breast cancer, confidence in breast self-examination; enabling factors: convenience in breast self-examination; and reinforcing factors: social support among women workers. Design: Descriptive correlational research. Methods: The study sample consisted of 116 women workers who worked at enterprises in Khoasaming District, Trat Province. Data were collected by means of administering a set of questionnaires: demographic characteristics, a knowledge of breast cancer, an attitude toward breast cancer, a confidence in breast selfexamination, a convenience in breast self-examination, and a social support. Relationships among the study variables were determined using Spearman’s rank correlation. Main findings: The study findings revealed that 11.2% of the women workers performed breast selfexamination on a monthly basis. More than half, or 55.2%, had a low level of correctness in breast selfexamination. It was also found that the factors of knowledge (r = .35, p < .001), confidence (r = .35, p < .001), convenience (r = .22, p < .05), and social support (r = .25, p < .05) were related to breast self-examination behaviors among women workers with statistical significance. However, there was no relationship between attitude toward breast cancer and breast self-examination behaviors among women workers. Conclusion and recommendations: Nurses in enterprises and related healthcare team members should promote knowledge of breast cancer, particularly breast self-examination methods, among women workers. Nurses should also encourage them to be confident in observing abnormalities of the breasts using palpation technique as well as facilitate advisory services in a hospital or staff rooms. Keywords: breast self-examination behaviors, women workers ปัจจัยที่มีความสัมพันธ์ต่อพฤติกรรมการตรวจเต้านมด้วยตนเองของสตรีวัยแรงงาน บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาความสัมพันธ์ระหว่างปัจจัยนำ ได้แก่ ความรู้เกี่ยวกับมะเร็งเต้านม ทัศนคติต่อมะเร็งเต้านม ความมั่นใจต่อการตรวจเต้านมด้วยตนเอง ปัจจัยเอื้อ ได้แก่ ความสะดวกในการตรวจเต้านมด้วยตนเอง และปัจจัยเสริม ได้แก่ แรงสนับสนุนทางสังคม กับพฤติกรรมการตรวจเต้านมด้วยตนเองของสตรีวัยแรงงาน รูปแบบการวิจัย: การวิจัยศึกษาความสัมพันธ์เชิงพรรณนา วิธีดำเนินการวิจัย: กลุ่มตัวอย่างคือ สตรีวัยแรงงานที่ทำงานในสถานประกอบกิจการ อำเภอเขาสมิง จังหวัดตราด จำนวน 116 คน เก็บรวบรวมข้อมูลโดยใช้แบบสอบถามข้อมูลทั่วไป ความรู้เกี่ยวกับมะเร็งเต้านม ทัศนคติต่อมะเร็งเต้านม ความมั่นใจต่อการตรวจเต้านมด้วยตนเอง ความสะดวกในการตรวจเต้านมด้วยตนเอง และการได้รับแรงสนับสนุนทางสังคม วิเคราะห์ความสัมพันธ์โดยใช้สถิติสหสัมพันธ์สเปียร์แมน ผลการวิจัย: สตรีวัยแรงงานตรวจเต้านมด้วยตนเองสม่ำเสมอทุกเดือนเพียงรอ้ ยละ 11.2 โดยตรวจถูกต้องในระดับ ต่ำร้อยละ 55.2 และพบตวั แปรที่มีความสัมพันธ์กับพฤติกรรมการตรวจเต้านมด้วยตนเองของสตรีวัยแรงงานอย่างมีนัยยสำคัญทางสถิติ ได้แก่ ความรู้เกี่ยวกับมะเร็งเต้านม (r = .35, p < .001) ความมั่นใจต่อการตรวจเต้านมด้วยตนเอง (r = .35, p < .001) ความสะดวกในการตรวจเต้านมด้วยตนเอง (r = .22, p < .05) แรงสนับสนุนทางสังคม (r = .25, p < .05) และไม่พบความสัมพันธ์ระหว่างทัศนคติต่อมะเร็งเต้านมกับพฤติกรรมการตรวจเต้านมด้วยตนเอง สรุปและข้อเสนอแนะ: พยาบาลประจำสถานประกอบกิจการหรือบุคลากรทีมสุขภาพที่เกี่ยวข้องควรมีการส่งเสริมให้ความรู้เกี่ยวกับมะเร็งเต้านม โดยเฉพาะวิธีการตรวจเต้านมด้วยตนเอง และเสริมสร้างความมั่นใจในประเด็นของการสังเกตความผิดปกติของเต้านม และการตรวจโดยการคลำ รวมทั้งจัดอำนวยความสะดวกโดยการหาแหล่งบริการคำแนะนำในห้องพยาบาลหรือห้องพักพนักงาน และประสานกับเจ้าของสถานประกอบกิจการเพื่อจัดกิจกรรมที่เหมาะสมกับสตรีวัยแรงงาน คำสำคัญ: พฤติกรรมการตรวจเต้านมด้วยตนเอง สตรีวัยแรงงาน